Effective Surface Passivation via Intermolecular Interactions for High‐Performance Perovskite Solar Cells. Issue 7 (12th April 2022) - Zhan, Jingbo; Li, Ming; Zhou, Zhongmin
Abstract : To reduce the surface defects of perovskite film and hole extraction loss, an organic small molecule, 1, 3‐dihydroxypropan‐2‐one (DHA), is introduced at the perovskite/hole transport layer interface. Fourier transform infrared spectroscopy is conducted to reveal the interactions (coordination and hydrogen bonding) between DHA and perovskite. A variety of characterizations (including photoluminescence (PL), time‐resolved photoluminescence (TRPL), electrochemical impedance spectroscopy (EIS), etc.) are performed to disclose the effect of DHA on device performance. Consequently, a high efficiency of 23.26% is obtained for the DHA‐treated device, while the control device shows only a companion efficiency of 20.21%. Moreover, the DHA‐treated devices exhibit improved storage and thermal stability. Abstract : Featuring two hydroxyls and one carbonyl, 1, 3‐dihydroxypropan‐2‐one is introduced to passivate the uncoordinated lead cations and organic components on the surface of perovskite films via coordination and hydrogen bonding interactions. The device efficiency is improved from 20.21% to 23.26%, as well as better storage and thermal stability.